Logical scheme based fight control strategies in martial arts: judo case study - Litmanovich, A. V.; Martin, A. A.; Razumov, V. I. (Theory and Practice of Physical Culture, 2018)
The study analyzes the fight control thinking patterns in terms of the object-barrier scheme, and offers different fight control strategies versus the specific tactical goals, with a fighter expected to process the input data flow so as to model the fight situations and respond by the most effective technical/ tactical solutions. In the modern situational sports on the whole and judo in particular, fight control problems often come up when an athlete tends to underestimate the importance of some provisionally specific isolated elements of the bout to respond by the standard elementary actions, and this underestimation may be detrimental for the technical/ tactical performance.